2020
DOI: 10.1080/15476286.2019.1710050
|View full text |Cite
|
Sign up to set email alerts
|

YB-3 substitutes YB-1 in global mRNA binding

Abstract: Y-box binding proteins are DNA-and RNA-binding proteins with an evolutionarily ancient and conserved cold shock domain. The Y-box binding protein 1 (YB-1) is the most studied due to its abundance in somatic cells. YB-1 is involved in a variety of cellular processes, including proliferation, differentiation and stress response. Here, using Ribo-Seq and RIP-Seq we confirm that YB-1 binds a wide range of mRNAs and globally acts as a translation inhibitor. Surprisingly, YBX1 knockout results in only minor alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 62 publications
(87 reference statements)
1
30
0
Order By: Relevance
“…Probably other YB proteins, such as YB-2 and YB-3, or other RBPs functionally compensate for the YB-1 loss. This hypothesis is supported by the observation of even more severe malformations and an earlier death of the YB-1 and MSY4 (mouse YB-3) double knockout embryos [104], as well as by the recent discovery of the functional interchangeability of YB-1 and YB-3 in HEK293T cells [79].…”
Section: Yb Proteins In Translation Inhibitionmentioning
confidence: 83%
See 4 more Smart Citations
“…Probably other YB proteins, such as YB-2 and YB-3, or other RBPs functionally compensate for the YB-1 loss. This hypothesis is supported by the observation of even more severe malformations and an earlier death of the YB-1 and MSY4 (mouse YB-3) double knockout embryos [104], as well as by the recent discovery of the functional interchangeability of YB-1 and YB-3 in HEK293T cells [79].…”
Section: Yb Proteins In Translation Inhibitionmentioning
confidence: 83%
“…For YB-3, eCLIP (enhanced CLIP) showed that it binds a broad set of specific RNAs without a discernible binding motif (8727 binding regions within 4018 RNAs) in HeLa cells [78]. In addition, the RIP-Seq (RNA Immunoprecipitation Sequencing) analysis showed that in HEK293T cells, the mRNA sets bound to YB-1 and YB-3 are almost the same, and they amount to about 80% of the transcriptome [79]. Yet, the specificity of these proteins is somewhat different.…”
Section: In Vivo Interactions Of Yb Proteins With Nucleic Acidsmentioning
confidence: 99%
See 3 more Smart Citations